Socio-Spiritual Capital Strategy of Street Vendors (PKL) in East Jakarta for Achieving Household Economic Resilience - Beti Nurbaiti; Chotib Chotib; Lita Aulia Putri (International Journal Labs, 2025)
This study aims to analyze how street vendors practice socio-spiritual capital in their daily lives to achieve economic resilience in their households. Representative respondents/informants were 3 person street vendors in East Jakarta. This research approach was qualitative using in-depth interviews, field observations, and participatory approach. The findings and results of the study indicate that in addition to the social capital practiced in the daily lives of street vendors, there is another aspect, namely spirituality, which colors their spirit of survival. Street vendors share and help each other selflessly with a spirit of doing good, with the belief that making things easier and helping others will later produce the same thing in the future because it is reciprocal. This belief is concluded as socio-spiritual capital is a novelty that integrates social and spiritual dimensions which has not been extensively studied in the context of urban informal sector workers. The study reveals that this socio-spiritual capital has a significant impact on the economic resilience of street vendors' households in East Jakarta. Practically, these findings imply that street vendor empowerment policies should not only focus on spatial planning and economic aspects, but also strengthen spiritual values and social solidarity as the foundation of household economic resilience.